2021
DOI: 10.3389/fimmu.2021.684967
|View full text |Cite
|
Sign up to set email alerts
|

Sterile Injury Repair and Adhesion Formation at Serosal Surfaces

Abstract: Most multicellular organisms have a major body cavity containing vital organs. This cavity is lined by a mucosa-like serosal surface and filled with serous fluid which suspends many immune cells. Injuries affecting the major body cavity are potentially life-threatening. Here we summarize evidence that unique damage detection and repair mechanisms have evolved to ensure immediate and swift repair of injuries at serosal surfaces. Furthermore, thousands of patients undergo surgery within the abdominal and thoraci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(41 citation statements)
references
References 163 publications
(233 reference statements)
0
41
0
Order By: Relevance
“…Adhesion is the body's excessive repair of tissue damage to some extent. Besides the aforementioned role of fibroblasts, they are also involved with the recruitment and activation of inflammatory cells [ 44 , 45 ]. Therefore, the anti-inflammatory effect of different materials was evaluated via the proliferation and differentiation of monocytes and the inflammatory factors secretion.…”
Section: Resultsmentioning
confidence: 99%
“…Adhesion is the body's excessive repair of tissue damage to some extent. Besides the aforementioned role of fibroblasts, they are also involved with the recruitment and activation of inflammatory cells [ 44 , 45 ]. Therefore, the anti-inflammatory effect of different materials was evaluated via the proliferation and differentiation of monocytes and the inflammatory factors secretion.…”
Section: Resultsmentioning
confidence: 99%
“…The inflammatory response at the damaged site is one of the mechanisms that causes adhesion formation, which stimulates the exudation of a large number of inflammatory mediators from the peritoneum or intestinal wall, further stimulating the exudation and deposition of fibrin in the damaged area and leading to the formation of dense adhesions [ 4 ]. Second, the inflammatory response affects the normal repair of peritoneal mesothelial cells, promotes the transformation of mesothelial cells to mesenchymal cells, and contributes to adhesion formation [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have identified that intraperitoneal adhesion formation contains several mutual interactive and overlapping processes such as coagulation and fibrinolysis, inflammation, cell proliferation, and fibrosis [ 3 ]. Multifarious cell types such as immunocytes (such as macrophages, monocytes, and mast cells), fibroblasts, and mesothelial cells are involved in the above process [ 4 ]. It is recently suggested that the severity of inflammation is closely and positively correlated with adhesion formation.…”
Section: Introductionmentioning
confidence: 99%
“…MCs modulate inflammation by synthesis and release of HA, which is able to sequester free radicals and initiate tissue repair responses [ 5 ]. Further, if HA and other extracellular matrix components constitutively present in the extracellular space are modified by injuries, they can become damage-associated molecular patterns—immune-stimulatory molecular patterns that can induce inflammation in case of sterile injury, recognized by CD44 receptor and others [ 4 , 5 ]. Moreover, failure to remove HA degradative products from sites of injury results in unremitting inflammation [ 31 ].…”
Section: Ha In Peritoneal Fibrosismentioning
confidence: 99%
“…The mesothelial-to-mesenchymal transition (MMT) consists of gradual loss of epithelial characteristics and the acquisition of myofibroblast-like phenotype. Subsequently, deposition of extracellular matrix (ECM) by myofibroblasts is induced and fibrotic tissue is formed among visceral organs [ 3 , 5 ].…”
Section: Introductionmentioning
confidence: 99%